2020 State of the Water Industry Survey Suggests Glass Half Full. Issue 6 (2nd June 2020) - Flancher, Dawn
Abstract : Before COVID‐19 became humanity's primary focus, water professionals expressed increased optimism for their industry's future in AWWA's 2020 State of the Water Industry (SOTWI) survey. Now in its 16th year, the survey closed in November 2019 with an unprecedented 3, 351 responses—up 39 percent from the previous year.